PENGARUH PEMBERIAN DOSIS PUPUK KANDANG SAPI DAN MULSA PADA PERTUMBUHAN DAN HASIL TANAMAN MELON ( Cucumis Melo L.) - Hartoyo Hartoyo (Universitas Islam Balitar, 2021)
This study aims to determine the effect of the best combination of cow manure and mulch on the growth and yield of melon plants (Cucumis melo L.). This study was conducted using a Randomized Group Design ( RAK) with 10 combinations of 3 repeats, the first factor of cow manure (P) consisting of cow manure 0 tons / ha (p1), 10 tons / ha (P2), 20 tons / ha (p3), 30 tons / ha (p4), 40 tons / ha (p5). for the second factor, namely mulch (M) which consists of silver color mulch ( M1) and without mulch ( M2). There is a noticeable influence on the combination of 30 tons/ha of cow manure and silver mulch (P4M1). The combined treatment of cow manure 30 – 40 tons /ha and silver mulch gives the best results against the growth and yield of melon plants (Cucumis melo L.).